Definitive and adjuvant radiation therapy for external auditory canal and temporal bone squamous cell carcinomas: Long term outcomes. (May 2022) - Laskar, Sarbani Ghosh; Sinha, Shwetabh; Pai, Prathamesh; Nair, Deepa; Budrukkar, Ashwini; Swain, Monali; Kumar, Anuj; Moiyadi, Aliasgar; Shetty, Prakash; Ray, Vedanta; Johnny, Carlton; Murthy, Vedang; et al.
Highlights: Institutional audit of 89 EAC Squamous Cell Carcinomas treated with RT. Improved late toxicity with IMRT as compared to conventional /3D-CRT technique. No nodal relapse in tumors where elective nodal RT was omitted post operatively. Out of 12 patients who received NACT, 8 could undergo surgery. Abstract: Introduction: Primary Squamous Cell Carcinoma (SCC) of the external auditory canal (EAC) and Temporal Bone (TB) are rare entities with very few large reports on outcomes and toxicities. Materials and methods: A retrospective audit of all SCC of EAC/TB tumors treated with curative intent RT at our Institute between January 2007 and December 2019 was undertaken. The primary endpoint of the study was event-free survival (EFS). Results: Eighty-nine patients were eligible for analysis. The median age was 54 years. The median follow-up of surviving patients was 61 months. Sixty-five patients received adjuvant RT, and 24 received definitive RT. Neoadjuvant Chemotherapy for aiding resectability was used in 12 patients, out of which 8 underwent surgery. The 5-year LRC, EFS, and OS were 66.2%, 57.8%, and 63.5%. The predominant pattern of failure was local ( n  = 36, 40.4%). Regional failure was seen in only five patients, none of which were in patients in whom elective nodal irradiation had been omitted post-operatively. On multivariable analysis adjuvant RT was associated with superior outcomes than definitive RT. Treatment with IMRT resulted in lower ≥ grade 2 late subcutaneous fibrosis (8.7% vs. 38.1%) compared to conventional/3D-CRT technique. Conclusions: Surgery followed by adjuvant therapy should remain the mainstay of treatment for EAC and TB SCC. IMRT should be the preferred modality for RT due to lower late morbidity. Elective nodal irradiation is routinely not warranted in the adjuvant setting for EAC and TB squamous cell carcinomas.